Effort to Increase Student Learning Interes through Spiritual Intelligence Values - Maryam, Siti (PT. Riset Press International, 2023)
The world of education as a center for forming good and quality human resources not only in terms of intelligence but emotionally and spiritually. The role of experts in the world of education is very important in the formation of quality human resources. The value of spiritual intelligence which is believed to be an intellectual and emotional balancer, builds life to be more meaningful and has psychological calm. Making students as individuals as well as possible, in all aspects, one of which is in the learning process. Interest in learning as one aspect of achieving good results. So in this study aims to examine efforts to increase students' interest in learning through the values of spiritual intelligence, with descriptive qualitative research on grade 3 students of MTs Darunna'im. Data collection through observation techniques, interviews and documentation is also supported by the results of analysis of primary and secondary data. Generating spiritual intelligence values possessed by students is very effective and influential in efforts to increase interest in learning.